Platylomia operculata Distant, 1913, a cicada that takes water from hot springs and becomes victim of the people (Rhynchota: Cicadomorpha: Cicadidae) - Boulard, Michel M. (Acta entomologica slovenica (Ljubljana), 2008)
Males of the Asian cicada Platylomia operculata Distant, 1913, mysteriously sense the need to absorb some water from rather frequent hot springs in North Thailand (notably those of Jaesorn National Park), and come to sources only atnight adding an unusual element to the behaviour of normally diurnal and crepuscular insects. This imperative followed in unison by the males of the same population, finds an anthropic and tragic end, the cicada in question representing a proteinic manna appreciated by Thais. In the addendum, we give a provisional list of the Jaesorn N.P. cicadofauna, of which two other speciestake some drinks from mud or humid sand (first records).
Keywords: Azija; entomologija; etologija; škržati; Tajska